Clarin‐2 is essential for hearing by maintaining stereocilia integrity and function. Issue 9 (26th August 2019) - Dunbar, Lucy A; Patni, Pranav; Aguilar, Carlos; Mburu, Philomena; Corns, Laura; Wells, Helena RR; Delmaghani, Sedigheh; Parker, Andrew; Johnson, Stuart; Williams, Debbie; Esapa, Christopher T; Simon, Michelle M; et al.
Abstract: Hearing relies on mechanically gated ion channels present in the actin‐rich stereocilia bundles at the apical surface of cochlear hair cells. Our knowledge of the mechanisms underlying the formation and maintenance of the sound‐receptive structure is limited. Utilizing a large‐scale forward genetic screen in mice, genome mapping and gene complementation tests, we identified Clrn2 as a new deafness gene. The Clrn2 clarinet / clarinet mice (p.Trp4* mutation) exhibit a progressive, early‐onset hearing loss, with no overt retinal deficits. Utilizing data from the UK Biobank study, we could show that CLRN2 is involved in human non‐syndromic progressive hearing loss. Our in‐depth morphological, molecular and functional investigations establish that while it is not required for initial formation of cochlear sensory hair cell stereocilia bundles, clarin‐2 is critical for maintaining normal bundle integrity and functioning. In the differentiating hair bundles, lack of clarin‐2 leads to loss of mechano‐electrical transduction, followed by selective progressive loss of the transducing stereocilia. Together, our findings demonstrate a key role for clarin‐2 in mammalian hearing, providing insights into the interplay between mechano‐electrical transduction and stereocilia maintenance. Synopsis: The study identifies CLRN2 as a new deafness gene required for maintenance of transducing stereocilia in the sensory cochlear hair cells. Lack of clarin‐2 leads to an early‐onset hearing loss in mice. CLRN2 is associated with human non‐syndromic progressive hearing loss. Utilizing an unbiased forward genetic screen in mice, a Clrn2 gene nonsense mutation (p.Trp4*) was identified as the cause of deafness in the clarinet mouse mutant ( Clrn2 clarinet ). Analysis of data from the UK Biobank study identifies CLRN2 as a novel candidate gene for human non‐syndromic progressive age‐related hearing loss. While clarin‐2 is non‐essential for stereocilia bundle patterning, it is indispensable for their maintenance, with loss of clarin‐2 leading to stereocilia resorption, decreased mechano‐electrical transduction, and progressive hearing impairment. Abstract : The study identifies Clarin‐2 as a new deafness gene required for maintenance of transducing stereocilia in the sensory cochlear hair cells. Lack of clarin‐2 leads to an early‐onset hearing loss in mice. CLRN2 is associated with human non‐syndromic progressive hearing loss.